A Needs-Based Support for #MeToo: Power and Morality Needs Shape Women’s and Men’s Support of the Campaign - Kende, Anna; Nyúl, Boglárka; Lantos, Nóra Anna; Hadarics, Márton; Petlitski, Diana; Kehl, Judith; Shnabel, Nurit (Frontiers in Psychology, 2020)
The #MeToo campaign mobilized millions of women around the world to draw attention to the pervasiveness of sexual harassment. We conducted an online survey in Hungary (N = 10,293) immediately at the campaign’s onset, and two subsequent studies in Israel and Germany (Ns = 356, 413) after it peaked, to reveal the motivations underlying people’s support for, or criticism of the campaign. Integrating the assumptions of the needs-based model of reconciliation and system justification theory, we predicted and found that, in all three samples, lower gender system justification was associated with (a) women’s perception of the campaign as empowering, and men’s (b) higher perception of the campaign as an opportunity for moral improvement, and (c) lower perception of the campaign as wrongfully staining men’s reputation. As expected, in all three samples, (a) perceptions of the campaign as empowering among women, and an opportunity for moral improvement among men, were associated with greater campaign support, whereas (b) men’s perceptions of the campaign as wrongfully staining their moral reputation were associated with lower campaign support. Thus, the link between system justification and campaign support was mediated by women’s empowerment needs, and men’s morality-related needs. In addition, perceptions of the campaign as disempowering their ingroup (i.e., presenting a status threat) predicted reduced campaign support among men in the Hungarian and Israeli samples, but not the German sample. We discuss the practical implications of these results for gender equality movements in general, and sexual harassment in particular, by identifying the psychological obstacles and catalysts of women’s and men’s support for social change.